Analysis of the Use of Coal Waste (Bottom Ash) As A Substitute For Aggregate in A Thin Layer Mix of Asphalt Concrete - Kardiman Kardiman; Sabaruddin Sabaruddin; Abdul Gaus (Eduvest - Journal of Universal Studies, 2022)
PLTU Tidore produces coal waste in the form of bottom ash or (FABA) which produces an average of 14 tons per day or 5,040 tons per year. To reduce the amount of waste, which can reduce production costs and reduce industrial waste, namely by using bottom ash as a substitute for fine aggregate. The specifications in the implementation of this test refer to the General Bina Marga 2018 specifications. The compaction of the test object is carried out in 2 × 75 collisions assuming that the test is intended for heavy traffic. The test results show that the bottom ash content as an aggregate substitute for fine aggregate produces a stability value of 1437 kg, flow 3.23 mm, MQ 450.11 kg/mm, density 2.377 gr/cm³, and porosity 4.71%. The values of flow, density, stability, MQ, porosity and porosity meet the requirements of the values set in Revision II of Highways (2018). ITS test of hot mixture HRS-BASE with the addition of bottom ash in the optimum asphalt content of 925.39 Kpa